2016
DOI: 10.2174/1568026616666160414122644
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2-a]pyridines: Promising Drug Candidate for Antitumor Therapy

Abstract: Imidazo[1,2-a]pyridine has been shown to be an important biologically active moiety. This review is a compilation of the scattered output of results of the anticancer activities of the imidazo[1,2-a]pyridine system since 2001, which have been classified as inhibition of CDK, VEGFR, PI3K, EGFR, RGGT etc. along with inhibition against different tumor cell lines. Various imidazo[1,2-a]pyridine based analogues have been used as lead molecules and are now under human clinical trials. This review will help the wider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…In particular, the imidazo[1,2-a]pyridine moieties of imidazopyridine have recently gained significant interest as potential anticancer agents due to their potent inhibitory role of cancer cell growth, which is commonly due to survival kinases inhibition (7,8). Various drugs containing imidazo[1,2-a]pyridine moieties are currently used to treat cardiac disorders, insomnia, antianxiety, ulcers and HIV infections (9). Although these compounds have numerous medicinal applications, none of them have been accepted as an anti-cancer drug.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the imidazo[1,2-a]pyridine moieties of imidazopyridine have recently gained significant interest as potential anticancer agents due to their potent inhibitory role of cancer cell growth, which is commonly due to survival kinases inhibition (7,8). Various drugs containing imidazo[1,2-a]pyridine moieties are currently used to treat cardiac disorders, insomnia, antianxiety, ulcers and HIV infections (9). Although these compounds have numerous medicinal applications, none of them have been accepted as an anti-cancer drug.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were also synthesized in the conventional method (7), and the yield of each compound was compared with the authentic samples. It has been observed that the yield of all the compounds was increased in microwaveassisted synthesis method.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds with the imidazo[1,2-a]pyridine scaffold exhibit a plethora of biological activities, including acting as receptor ligands, anti-infectious agents, enzyme inhibitors etc. as well as being potential nitrogen heterobicycle therapeutic agents, as described by recent studies (Goel et al, 2016;Deep et al, 2017;Kuthyala et al, 2018). On the other hand, compounds containing the 1,3-dithiolan-2-ylidene moiety have been found to exhibit valuable pharmacological activities, including use as potent broad-spectrum fungicides (Tanaka et al, 1976, Wang et al, 1994, antitumor agents (Huang et al, 2009), potent cephalosporinase inhibitors (Ohya et al, 1982) and anti-HIV agents (Nguyen-Ba et al, 1999;Besra et al, 2005).…”
Section: Chemical Contextmentioning
confidence: 99%